Multicenter study on the prevalence of colonization due to carbapenem-resistant Enterobacterales strains before and during the first year of COVID-19, Italy 2018–2020 - Fasciana, Teresa; Antonelli, Alberto; Bianco, Gabriele; Lombardo, Donatella; Codda, Giulia; Roscetto, Emanuela; Perez, Marianna; Lipari, Dario; Arrigo, Ignazio; Galia, Elena; Tricoli, Maria Rita; Calvo, Maddalena; et al. (Frontiers in Public Health, 2023)
Background: Among multidrug-resistant (MDR) bacteria able to threaten human health, carbapenem-resistant Enterobacterales (CRE) have become a major public health threat globally.National and international guidelines point out the importance of active routine surveillance policies to prevent CRE transmission. Therefore, defining lines of intervention and strategies capable of containing and controlling the spread of CRE is considered determinant. CRE screening is one of the main actions to curb transmission and control outbreaks, outlining the presence and also the prevalence and types of carbapenemase enzymes circulating locally.The purpose of this study was to outline the epidemiology of CRE colonization in Italy, detecting CRE-colonized patients at admission and during hospitalization, before and during the first year of COVID-19.A total of 11,063 patients admitted to seven different hospitals (Bologna,